2021
DOI: 10.1186/s12884-021-04147-z
|View full text |Cite
|
Sign up to set email alerts
|

Tanzanian men’s engagement in household chores is associated with improved antenatal care seeking and maternal health

Abstract: Background Male support for partners’ antenatal care (ANC) has the potential to improve women’s care-seeking and maternal health outcomes. This study describes factors that are associated with men’s involvement in household tasks and explores the relationship between men’s help with tasks and women’s ANC-seeking, diet and workload during pregnancy as well as other health behaviors. Methods This study was conducted in five Lake Zone regions of Tanza… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…Likewise, the literature shows a consensus that the participation rate of men in domestic chores has increased (Akanle et al, 2016). This is clearer in a study by Chahalis et al, (2021) in Tanzania, where it was found that male participation in household chores contributes to improved early childhood development. This is despite the fact that traditions often place men in charge of family finances.…”
Section: Expansionist Theorymentioning
confidence: 94%
See 1 more Smart Citation
“…Likewise, the literature shows a consensus that the participation rate of men in domestic chores has increased (Akanle et al, 2016). This is clearer in a study by Chahalis et al, (2021) in Tanzania, where it was found that male participation in household chores contributes to improved early childhood development. This is despite the fact that traditions often place men in charge of family finances.…”
Section: Expansionist Theorymentioning
confidence: 94%
“…The literature highlights an interesting watershed regarding gender aspects over time where it is shown that the roles of women and men have been diversifying and it is clear we are now observing a greater involvement of women in work activities and men in domestic activities (Anbacha and Kjosavik, 2021;Chahalis et al, 2021). Therefore, it is interesting to analyze the craft sector through the lens of expansionist theory to explain gender aspects in current times and provide elements that allow a greater understanding of this sector.…”
Section: Expansionist Theorymentioning
confidence: 99%
“…Men had reduced their household workload during their partners’ most recent pregnancies and were more likely to have played with their children in the week prior to the survey. Chahalis et al, 2021 [ 40 ] 4217 men, 4091 women Quality: 5 24 Husbands’ experience and perception of supporting their wives during childbirth in Tanzania. Qualitative To explore the experience and perceptions of husbands’ support for their wives during pregnancy, labour and delivery in Tanzania Tanzania Husbands who supported their partners during pregnancy and delivery saw themselves as modern since, at home, they undertook chores besides their usual tasks to allow their wives adequate time to rest during pregnancy.…”
Section: Methodsmentioning
confidence: 99%
“…IMA partnered with Development Media International (DMI)-its partner in the development and implementation of radio and TV spots-to design and conduct baseline, midline, and endline surveys to inform program direction and to assess impact during, in the middle, and at the end of the program. Numerous studies exploring the associations of key health outcomes and exposure to core program elements and indicators at either baseline, midline, or endline have been published previously [9][10][11][12][13][14][15][16][17][18]. Associations between knowledge of key health-promoting behaviors included in SBCC programming and stunting prevention have been significant [10,13,15].…”
Section: Introductionmentioning
confidence: 99%
“…In particular, a mother's exposure to the SBCC's IPC programming was positively associated with all measured ECD behaviors, including talking to, drawing with, counting with, naming objects with, and playing with your child. Similarly, previous analyses of ASTUTE data have also explored the impact of key SBCC programming related to male involvement, including maternal perceptions of the role of men during pregnancy [16] and associations between men's engagement in household chores and both maternal health and ANC-seeking behaviors [12]. However, to date, no study has provided a comprehensive analysis inclusive of both mass media and IPC programming using baseline, midline, and endline ASTUTE data.…”
Section: Introductionmentioning
confidence: 99%